A new bioleaching strategy for the selective recovery of aluminum from multi-layer beverage cans. (1st February 2021) - Kremser, Klemens; Gerl, Patrick; Pellis, Alessandro; Guebitz, Georg M.
Graphical abstract: Highlights: Bioleaching was applied for the separation of multi-layer packaging materials. Selective aluminum recovery was obtained from used beverage cans. Separation of epoxy resin and aluminum was achieved. New application of bioleaching bacteria used for recycling. Abstract: Used beverage cans (UBĆs) represent one of the largest sources for secondary aluminum production worldwide. Beverage cans are one of the most frequently produced multi-layer packaging materials made of aluminum with an inner epoxy resin coating to prevent direct contact of food and aluminum surface. In the common way of UBĆs recycling, the whole can is re-melted, resulting in the burning and loss of the inner epoxy coating. The use of acidophilic bacteria for the biological leaching of metals has already been well studied, but until now their applications for the selective separation of metal-containing multilayer materials has not been investigated. In this study, the three bioleaching bacteria: A. ferrooxidans, A. thiooxidans and A. caldus were explored to selectively leach the aluminum from the epoxy layer, resulting in leaching efficiencies of around 92% after three weeks of incubation. Surface characterization of the epoxy layer after bioleaching application revealed that the nature of the epoxy resin was unchanged, which could allow for recycling. The dissolved aluminum was afterwards selectively precipitated from the lixiviants at pH = 6.5, resulting in aluminum hydroxide precipitation efficiencies of almost 100%. The high leaching efficiencies and the selective precipitation shows the significant potential of acidophilic bacteria in the separation and recycling of multi-layer materials.